A decision modelling approach for selection of biological nutrient removal systems for wastewater - Pausta, Carla Mae (Animo Repository, 2018)
This paper proposes a decision model built on a hierarchical network for optimal selection of biological nutrient removal systems (BNR) in wastewater treatment plants. BNR is an important component of a sustainable wastewater management wherein resource recovery from wastewater becomes an integral part of the municipal wastewater treatment plants (WTP). However, selection of the most appropriate technology or systems requires a multiple criteria analysis. This study focuses on the following criteria namely 1) Economic aspect; 2) Technical aspect; 3) Environmental Aspect; and 4) Space Requirement. The following alternatives were then evaluated: 1) 3 Stage Pho-redox (A2O); 2) 5 Stage Bardenpho (5BP); 3) University of Cape Town (UCT); 4) Virginia Initiative Plant; 5) Sequencing Batch Reactor (SBR); 6) Membrane Bioreactor (MBR). A fuzzy ANP approach with Monte Carlo simulation was used to derive the overall priorities of these alternatives. This decision modelling approach addresses the uncertainty and complexity involved in the selection of appropriate BNR in Metro Manila's WTP. © The Authors, published by EDP Sciences, 2018.